The role of magnetic fields in neurodegenerative diseases - Riancho, Javier; Sanchez de la Torre, Jose Ramón; Paz-Fajardo, Lucía; Limia, Cristina; Santurtun, Ana; Cifra, Michal; Kourtidis, Kostas; Fdez-Arroyabe, Pablo (International journal of biometeorology, 2021)
The term neurodegenerative diseases include a long list of diseases affecting the nervous system that are characterized by the degeneration of different neurological structures. Among them, Alzheimer disease (AD), Parkinson disease (PD), and amyotrophic lateral sclerosis (ALS) are the most representative ones. The vast majority of cases are sporadic and results from the interaction of genes and environmental factors in genetically predisposed individuals. Among environmental conditions, electromagnetic field exposure has begun to be assessed as a potential risk factor for neurodegeneration. In this review, we discuss the existing literature regarding electromagnetic fields and neurodegenerative diseases. Epidemiological studies in AD, PD, and ALS have shown discordant results; thus, a clear correlation between electromagnetic exposure and neurodegeneration has not been demonstrated. In addition, we discuss the role of electromagnetic radiation as a potential non-invasive therapeutic strategy for some neurodegenerative diseases, particularly for PD and AD.
Keywords: amyotrofická laterální skleróza; Parkinsonova nemoc; Alzheimerova nemoc; Parkinson’s disease; Amyotrophic Lateral Sclerosis; Alzheimer Disease; neurodegenerativní nemoci; Humans; Amyotrophic lateral sclerosis; Neurodegenerative diseases; Electromagnetic fields; Electromagnetic Fields; Alzheimer’s disease; Neurodegenerative Diseases; lidé; elektromagnetická pole; Parkinson Disease